2017
DOI: 10.1136/bcr-2016-218469
|View full text |Cite
|
Sign up to set email alerts
|

Antimitochondrial antibodies-positive myositis accompanied by cardiac involvement

Abstract: We report a 55-year-old man who experienced proximal muscle weakness accompanied by the atrial flutter (AFL) with 1:1 conduction. Detailed examination revealed elevated antimitochondrial antibodies (AMA) and creatine kinase (CK). AFL was converted to sinus rhythm by cardioversion. He was diagnosed as AMA-positive myositis-associated AFL and was treated by prednisolone. Although his muscle weakness and CK level improved, AFL with 1:1 conduction reappeared. Therefore, radiofrequency catheter ablation (RFCA) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Indeed, we found that the clinical features in patients with AMAs showed great variability. Firstly, although AMAs only occurred in adult IIM patients, the age at onset ranged from 23 years to 86 years and the mean age at onset ranged from the fourth decade to the seventh decade [3][4][5]7,8,[20][21][22][23][24][25][26] . Besides, the average disease duration varied from 10 months (in our study) to 6.5 years, and the prevalence of chronic disease duration varied from approximately 30% (in our study) to 85% [3,5,6] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that the clinical features in patients with AMAs showed great variability. Firstly, although AMAs only occurred in adult IIM patients, the age at onset ranged from 23 years to 86 years and the mean age at onset ranged from the fourth decade to the seventh decade [3][4][5]7,8,[20][21][22][23][24][25][26] . Besides, the average disease duration varied from 10 months (in our study) to 6.5 years, and the prevalence of chronic disease duration varied from approximately 30% (in our study) to 85% [3,5,6] .…”
Section: Discussionmentioning
confidence: 99%
“…Although AMAs are most commonly found in association with PBC, the presence of the antibody has been linked to other autoimmune conditions, such as Sjögren's syndrome, scleroderma, and autoimmune thyroid disease ( 2 ). Inflammatory myopathy occurring in association with AMA is rare, but there has been growing recognition for this clinical entity ( 3 - 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids are considered as the first-line therapy for dermatomyositis, polymyositis, and IMNM ( 6 , 8 , 10 ). However, there is no established treatment for AMA-associated myopathy with cardiac involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the initially sparse muscle symptoms and prolonged diagnostic process with step-wise exclusion of genetic -, other rheumatic-, ischemic- and malignant diseases, before AMA testing provided a final diagnosis, caused a treatment delay, which might in part explain the insufficient cardiac responsiveness to immune suppressants in our patient. However, a diminished cardiac versus muscular response to immunosuppressants in AMA-IM has been observed in previous cases, across genders, disease durations and drug types [ 1 , 2 , 4 , 5 ]. Taken together, this might point to a need for more aggressive strategies to reverse the cardiac manifestations.…”
Section: Discussionmentioning
confidence: 77%